Changes in Electrokinetic Coupling Coefficients of Granite under Triaxial Deformation - Osamu Kuwano; Shingo Yoshida (International Journal of Geophysics)
Electrokinetic phenomena are believed to be the most likely origin of electromagnetic signals preceding or accompanying earthquakes. The intensity of the source current due to the electrokinetic phenomena is determined by the fluid flux and the electrokinetic coupling coefficient called streaming current coefficient; therefore, how the coefficient changes before rupture is essential. Here, we show how the electrokinetic coefficients change during the rock deformation experiment up to failure. The streaming current coefficient did not increase before failure, but continued to decrease up to failure, which is explained in terms of the elastic closure of capillary. On the other hand, the streaming potential coefficient, which is the product of the streaming current coefficient and bulk resistivity of the rock, increased at the onset of dilatancy. It may be due to change in bulk resistivity. Our result indicates that the zeta potential of the newly created surface does not change so much from that of the preexisting fluid rock interface.